MicroRNAs for the Diagnosis and Management of Malignant Pleural Mesothelioma: A Literature Review - Lo Russo, Giuseppe; Tessari, Anna; Capece, Marina; Galli, Giulia; de Braud, Filippo; Garassino, Marina Chiara; Palmieri, Dario (Frontiers in Oncology, 2018)
Malignant pleural mesothelioma is a rare and aggressive tumor with a variable incidence among different countries. Occupational asbestos exposure is the most important etiological factor and a very long latency period is widely reported. In the early phase of disease, clinical signs are absent or not specific. For this reason, the diagnosis is frequently achieved only in the advanced stages. The hystopathological diagnosis per se is also very complex, and not known factors can predict the prognosis with certainty. The standard treatment includes surgery, radiotherapy and chemotherapy, but current survival rates remain very low. The identification of new prognostic and/or diagnostic biomarkers, and the discovery of therapeutic targets is a priority and could lead to a real significant impact on the management of malignant pleural mesothelioma. In this scenario the role of microRNAs is becoming increasingly relevant, with the promise of a quick translation in the current clinical practice.